Effect of Helicobacter pylori eradication on the natural history of duodenal ulcer disease. Issue 6 (1st December 1998) - Goggin, N; Rowland, M; Imrie, C; Walsh, D; Clyne, M; Drumm, B
Abstract : BACKGROUND: Duodenal ulcer disease is strongly associated with Helicobacter pylori infection of the gastric mucosa. Eradication of H pylori from the gastric mucosa in adults is associated with long term healing of ulcers. AIMS: To follow a cohort of children with duodenal ulcer disease for a minimum of two years after the eradication of H pylori . PATIENTS AND METHODS: Over a three year period, all children diagnosed with duodenal ulcer disease had their symptoms documented and their H pylori status evaluated. The histories of these children were carefully screened to determine previous symptoms and to document previous treatment regimens. RESULTS: Sixteen children were diagnosed with ulcers and 15 were available for treatment and long term follow up. The median age at which symptoms first occurred was 10.5 years (range, 6–14) and the median duration of symptoms was 24 months (range, 2–60). Ten of the children had been treated with H2 receptor antagonists for a median of 3.5 months (range, 1–60). Duodenal ulcers healed in all children after eradication of H pylori and all children have remained asymptomatic for a median of 37 months (range, 26–62). No child has required subsequent admission to hospital. CONCLUSION: Eradication of H pylori is very effective in the long term healing of duodenal ulcer disease. H pylori eradication should be the standard treatment for all infected children who present with duodenal ulcer disease.